دور العلاقات العامة المالية " البنك الوطني الجزائري انموذجا " - شداد محمد رفيق; دهينة الرق; د/ مراح سميرة (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة باللغة العربية: تعد العلاقات العامة في المؤسسة المالية موضوعا جديرا بالبحث و الدراسة ويرجع ذلك إلى تعاظم أهمية كسب ثقة الجمهور، وتأييده في نجاح أية منظمة أو مؤسسة بصرف النظر عن نوع نشاطها، كما يرجعذلك إلى نمو شعور الإدارة العليا بمسؤولياتها وضرورة أخذ وجهة النظر العامة للعلاقات تتغير رئيسي مؤثر عند إتخاذ قراراتها ولذلك تلعب العلاقات العامة دوراً كبيراً في العصر الحديث، وكان للتقدم العلمي والتقني وتنوع وسائل الإعلام والاتصال تأثير كبير في زيادة أهمية العلاقات العامة وفاعليتها، فالعلاقات العامة لم تعد عبارة عن وظيفة يقوم بها موظف على أساس مواهبه وقدراته المهنية وهذا ما جعل منها ضرورة حتمية في مؤسساتنا المالية في ظل معطيات الفكر الاقتصادي الحديث، ونظرا لهذا جاءت هذه الدراسة كمحاولة لتوضيح الدور الفعال للعلاقات العامة في بنك الوطني الجزائري، خاصة في وقتنا الحالي أن معظم المؤسسات المالية إن لم نقل كلها بأمس الحاجة لإدارة فعالة للعلاقات العامة وذلك شريطة أن تعطى لها كامل المكانة التي تسمح لها بمزاولة مهامها على أكمل وجه. Studysummary: Public relations in the financial institution is a topic worthy ofresearch and study. This is due to the increasing importance of gaining thepublic’s trust and support in the success of any organization or institution،regardless of its type of activity. This is due to the growth of seniormanagement’s sense of its responsibilities and the necessity of taking thegeneral point of view of relations as a major influence when making itsdecisions. Therefore، public relations plays a major role in the modern era. Scientific and technical progress and the diversity of media and communicationhave had a great impact in increasing the importance and effectiveness ofpublic relations. Public relations is no longer It is a job performed by anemployee on the basis of his professional talents and abilities، and this iswhat made it an inevitable necessity in our financial institutions in light ofthe data of modern economic thought.In view of this، this study cameas an attempt to clarify the effective role of public relations in the NationalBank of Algeria، especially in our current time، as most، if not all، financialinstitutions are in dire need of effective management of public relations،provided that they are given the full position that allows them to carry outtheir duties to the fullest extent.